Nucleobindin 2/nesfatin‐1 expression and colocalisation with neuropeptide Y and cocaine‐ and amphetamine‐regulated transcript in the human brainstem. (9th September 2020) - Psilopanagioti, Aristea; Makrygianni, Maria; Nikou, Sofia; Logotheti, Souzana; Papadaki, Helen
Abstract: Feeding is a complex behaviour entailing elaborate interactions between forebrain, hypothalamic and brainstem neuronal circuits via multiple orexigenic and anorexigenic neuropeptides. Nucleobindin‐2 (NUCB2)/nesfatin‐1 is a negative regulator of food intake and body weight with a widespread distribution in rodent brainstem nuclei. However, its localisation pattern in the human brainstem is unknown. The present study aimed to explore NUCB2/nesfatin‐1 immunoexpression in human brainstem nuclei and its possible correlation with body weight. Sections of human brainstem from 20 autopsy cases (13 males, seven females; eight normal weight, six overweight, six obese) were examined using immunohistochemistry and double immunofluorescence labelling. Strong immunoreactivity for NUCB2/nesfatin‐1 was displayed in various brainstem areas, including the locus coeruleus, medial and lateral parabrachial nuclei, pontine nuclei, raphe nuclei, nucleus of the solitary tract, dorsal motor nucleus of vagus (10N), area postrema, hypoglossal nucleus, reticular formation, inferior olive, cuneate nucleus, and spinal trigeminal nucleus. NUCB2/nesfatin‐1 was shown to extensively colocalise with neuropeptide Y and cocaine‐ and amphetamine‐regulated transcript in the locus coeruleus, dorsal raphe nucleus and solitary tract. Interestingly, in the examined cases, NUCB2/nesfatin‐1 protein expression was lower in obese than normal weight subjects in the solitary tract ( P = 0.020). The findings of the present study provide neuroanatomical support for a role for NUCB2/nesfatin‐1 in feeding behaviour and energy balance. The widespread distribution of NUCB2/nesfatin‐1 in the human brainstem nuclei may be indicative of its pleiotropic effects on autonomic, neuroendocrine and behavioural processes. In the solitary tract, a key integrator of energy status, altered neurochemistry may contribute to obesity. Further research is necessary to decipher human brainstem energy homeostasis circuitry, which, despite its importance, remains inadequately characterised. Abstract : NUCB2/nesfatin‐1‐immunoreactive neurons are extensively localized in the human brainstem, with a distribution pattern encompassing energy balance control systems, autonomic regulatory centers, and stress‐related circuitries. In locus coeruleus, dorsal raphe nucleus, and nucleus of the solitary tract, NUCB2/nesfatin‐1 colocalized with neuropeptide Y and cocaine‐ and amphetamine‐regulated transcript, neuropeptides known to exert potent actions in metabolic, endocrine, and behavioral processes. Interestingly, in nucleus of the solitary tract, an essential portal integrating ingestion‐related signals to influence food intake, NUCB2/nesfatin‐1 immunoexpression was lower in obese than normal weight subjects.